Penguatan Kapasitas Aparatur Desa Melalui Bimbingan Teknis Pengelolaan Pemerintahan Dan Keuangan Desa Di Kabupaten Kuantan Singingi - Erwin, Muhammad (Journal of Community Sustainability, 2025)
This community service activity aims to strengthen the capacity of village officials in managing village governance and village finances in order to create effective, efficient, transparent, and accountable village governance in Kuantan Singingi Regency. The main problems faced by village officials include limited understanding of regulations and insufficient technical skills in managing governmental administration and village financial management. The activity was implemented through technical guidance conducted over three days, from October 3 to 5, 2024, at Hotel Jatra Pekanbaru. The methods used included lectures, interactive discussions, case studies, and question-and-answer sessions, involving resource persons from the Ministry of Home Affairs of the Republic of Indonesia (Central Office, Jakarta). The results of the activity indicate an improvement in the understanding and competence of village officials in planning, budgeting, administration, reporting, and accountability of village finances. In addition, the activity also promoted a shared understanding and increased awareness among village officials regarding the importance of transparency and accountability principles in the administration of village governance.